2015
DOI: 10.1016/j.enconman.2015.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Probability distributions of wind speed in the UAE

Abstract: a b s t r a c tFor the evaluation of wind energy potential, probability density functions (pdfs) are usually used to describe wind speed distributions. The selection of the appropriate pdf reduces the wind power estimation error. The most widely used pdf for wind energy applications is the 2-parameter Weibull probability density function. In this study, a selection of pdfs are used to model hourly wind speed data recorded at 9 stations in the United Arab Emirates (UAE). Models used include parametric models, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(98 citation statements)
references
References 61 publications
1
91
0
1
Order By: Relevance
“…Another method is to calculate the wind power density using frequency distribution functions like Weibull distribution, Rayleigh distribution, chisquared distribution, generalized normal, log normal-distribution, three parameter log-normal, gamma distribution, inverse Gaussian distribution, kappa, wakeby, normal two variable distributions, normal square root of wind speed distribution, as well as hybrid distribution [19] [21]. Researches have shown that Weibull function fits the wind probability distribution more accurately compared to others [22]. Here the author uses Weibull and Rayleigh distribution to fit the time series data.…”
Section: Wind Speed Probability Distributionmentioning
confidence: 99%
“…Another method is to calculate the wind power density using frequency distribution functions like Weibull distribution, Rayleigh distribution, chisquared distribution, generalized normal, log normal-distribution, three parameter log-normal, gamma distribution, inverse Gaussian distribution, kappa, wakeby, normal two variable distributions, normal square root of wind speed distribution, as well as hybrid distribution [19] [21]. Researches have shown that Weibull function fits the wind probability distribution more accurately compared to others [22]. Here the author uses Weibull and Rayleigh distribution to fit the time series data.…”
Section: Wind Speed Probability Distributionmentioning
confidence: 99%
“…Their speed rarely exceeds 10 m/s and stronger winds do not sustain for long duration. (Elshorbagy et al 2013;Ouarda et al 2015). …”
Section: Winds In Uaementioning
confidence: 99%
“…Ouarda et al [18] evaluated the wind speed with reference to probability density function and concluded the selection of appropriate pdf to minimize the wind power estimation error. The author used two-parameter Weibull distribution function, parametric models, mixture models, and one nonparametric method using kernel density method.…”
Section: Literature Reviewmentioning
confidence: 99%